Influence of the variation in radiographic technique on the digital radiographic image reading in interproximal alveolar bone resorption evaluation - Orivaldo Tavano; José Peixoto Ferrão Junior; Pedro Gregol da Silva (Faculdade São Leopoldo Mandic, 2009)
Objective: To analyze digital radiographic images using the resources available in the Digora digital radiograph system (Soredex, Helsinki, Finland), and comparing it with real images of the open surgical site, varying the angles of radiographs taken with the aim of obtaining a result closer to that which would be real. Methods: For the clinical exam, millimetric probes were used with the aid of a line that joins the amelocemental junction, measuring up to the center of the bone defect between two contiguous teeth. The radiographic exam was standardized to obtain a digital image with greater detail and the minimum of distortion, using a support and Rinn type positioner, and a resin model of the occlusal surfaces of the teeth to be radiographed, to reproduce the focus/film distances of 40cm, and object/film parallelism, in the five radiographic incidences used(0°, +10°, -10°, 10° to the right and 10° to the left).Results: After the descriptive statistical result the coefficient of variation was obtained, which was shown to be only regular, as it was over 20%. As regards the type of image treatment, DFW 2.5.a showed the standard radiograph to have similar results to those of the clinical exam, the 3D radiographic image had variations towards lower values and the negative images towards higher values. Conclusion: The standardization used in the research for radiographic exam showed that there is always a small enlargement of the image in relation to the clinical measurements; that the standard image was more reliable for the observation and measurement of interdental bone crests, followed by the 3D image and finally the negative image of the Digora digital radiographic system. The best incidence of X-rays, using the Rinn type positioner, is that of 0°, after this +10°, -10° and 10° to the right; the incidence of 10 to the left showed the greatest variation.